2014
DOI: 10.2147/ott.s36873
|View full text |Cite
|
Sign up to set email alerts
|

Considering the role of radiation therapy for gastrointestinal stromal tumor

Abstract: Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors arising in the gastrointestinal tract. Over the last decade, the management and prognosis of GISTs has changed dramatically with molecular characterization of the c-kit mutation and the adoption of targeted systemic therapy. Currently, the standard of care for resectable tumors is surgery, followed by adjuvant imatinib for tumors at high risk for recurrence. Inoperable or metastatic tumors are treated primarily with imatinib. Despite excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Randomized clinical trials showed increased rates of recurrence in patients when IM is discontinued. This led to the belief that IM has a “cytostatic” activity [44]. Therefore, patients will have to remain on IM therapy for long periods of time to delay recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trials showed increased rates of recurrence in patients when IM is discontinued. This led to the belief that IM has a “cytostatic” activity [44]. Therefore, patients will have to remain on IM therapy for long periods of time to delay recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Though long considered radioresistant, GIST metastases can be effectively palliated by RT [ 85 87 ]. In a prospective study of 25 patients with TKI-refractory GIST, 80% had stability of target lesions lasting a median of 16 months and median OS was 19 months [ 87 ].…”
Section: Locoregional Therapy For Metastatic Diseasementioning
confidence: 99%
“…Currently, GISTs are typically treated with resection and adjuvant therapy with tyrosine kinase inhibitors (TKIs) at high risk for recurrence (4,5). Unresectable or metastatic tumors are treated primarily by TKIs therapy (6,7). Under the current treatment guidelines, radiotherapy is not a recommended option, or is only used for palliative intent of bone metastases (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, radiotherapy for GISTs was still limited to dose-limiting toxicity of the adjacent small bowel. In recent years, intensity-modulated radiation therapy (IMRT), image-guided radiation therapy (IGRT) and other technological advances has realized dose escalation in target volume and potential reduction in acute and delayed toxicity by facilitating treatment delivery and normal tissue protection (6). Moreover, simultaneous integrated boost intensity-modulated radiation therapy (SIB-IMRT) can deliver the highest possible dose to target volume and increase tumor response without significant increase of healthy tissue irradiation (16,17).…”
Section: Introductionmentioning
confidence: 99%